Biomass-based efficient adsorbent as well as preparation method and application thereof
By reacting sodium lignin sulfate with chitosan quaternary ammonium salt with isocyanate and catalyst at a specific temperature, a composite high-efficiency adsorbent with a synergistic adsorption effect was constructed, solving the problems of high cost and insufficient performance of traditional adsorbent materials, and achieving efficient removal of acidic red dyes in dye wastewater.
Patent Information
- Application Number
- CN202411940483.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional adsorption materials such as activated carbon have high costs, difficulty in regeneration and potential secondary pollution when treating dye wastewater, and chitosan quaternary ammonium salts have low solubility and insufficient adsorption performance in acidic environments.
By reacting sodium lignin sulfate with chitosan quaternary ammonium salt at a specific temperature, combining isocyanate and catalyst, a composite high-efficiency adsorbent with a synergistic adsorption effect is constructed. This adsorbent significantly improves adsorption performance and structural stability through interaction mechanisms such as hydrogen bonds, ion bonds and π-π stacking effects.
It has achieved efficient removal of acidic red dyes, with an adsorption amount of up to 192 mg/g, reducing production costs, and expanding the applicable pH window of adsorbent materials and the processing capacity of different types of dyes.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and in particular to a biomass-based high-efficiency adsorbent and a preparation method and application thereof. Background Art
[0002] The large amount of dye wastewater generated during the production process of the textile, papermaking, printing and other industries has caused serious harm to the ecological environment and human health. After the dye molecules are discharged into the water body, they will reduce the light transmittance of the water body and affect the photosynthesis of the aquatic ecosystem. At the same time, their complex structure is difficult to be degraded by the natural environment. They will accumulate along the food chain through bioaccumulation, and ultimately threaten human health. Solving the above-mentioned water resource pollution problems caused by dye discharge is of great significance for restoring water cleanliness and protecting water resources.
[0003] The methods for treating wastewater are mainly divided into physical treatment, chemical treatment and microbial treatment. Among them, physical adsorption is widely studied and applied due to its advantages such as simple operation, high adsorption efficiency and wide application range. This method captures dye molecules through the microporous structure and chemical activity on the surface of the adsorbent material, thereby purifying the water body. However, although traditional adsorbent materials such as activated carbon have strong adsorption capacity, their high cost, difficulty in regeneration and potential secondary pollution problems limit their large-scale use, which has prompted researchers to continuously explore new adsorbent materials that are more economical, environmentally friendly and efficient.
[0004] Chitosan quaternary ammonium salt is a renewable resource derived from biomass. In recent years, it has received extensive attention in the field of organic dye wastewater treatment. The amino (-NH2) and hydroxyl (-OH) groups on its molecular chain can interact with dye molecules through electrostatic adsorption and hydrogen bonding, thereby effectively removing dyes from wastewater. Chitosan quaternary ammonium salt has become an important research object for biomass adsorption materials due to its low cost, high adsorption efficiency and abundant sources. However, there are still significant limitations in its application. In an acidic environment, most chitosan quaternary ammonium salts exist in a non-ionic form, which is difficult to interact effectively with water molecules, thereby significantly reducing its solubility and affecting its adsorption performance. In addition, chitosan quaternary ammonium salts are prone to agglomeration in aqueous solutions, further limiting their practical application range.
[0005] To overcome these shortcomings, scientific research has gradually turned to the grafting modification of chitosan quaternary ammonium salts, increasing its adsorption sites by introducing other functional groups and improving its solubility and adsorption performance under acidic conditions. This modification strategy can optimize its interaction mechanism with dye molecules, while expanding its applicable pH window and improving its ability to treat different types of dyes. These improvements can not only increase the application potential of chitosan quaternary ammonium salts in organic dye wastewater treatment, but also provide a new technical path for green development and environmental protection. Summary of the invention
[0006] In view of the above deficiencies in the prior art, the present invention provides a low-cost, biomass-based, efficient adsorbent and a preparation method and application thereof.
[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0008] In a first aspect, the present invention provides a method for preparing a biomass-based high-efficiency adsorbent, comprising the following steps:
[0009] S1, mixing sodium lignin sulfate and an organic solvent evenly to obtain sodium lignin sulfate slurry, recorded as slurry A;
[0010] S2, mixing chitosan quaternary ammonium salt and organic solvent uniformly to obtain chitosan quaternary ammonium salt slurry, recorded as slurry B;
[0011] S3. Under the protection of inert gas, the slurry A and the slurry B are mixed evenly, and then isocyanate and a catalyst are added. After reacting at 100-110° C., the mixture is filtered, washed, dried, ground, and sieved to obtain a biomass-based high-efficiency adsorbent.
[0012] The present invention aims at the problem that chitosan quaternary ammonium salt has low solubility and insufficient adsorption performance in an acidic environment. The present invention reacts a specific ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, isocyanate, and dibutyltin dilaurate at a specific temperature to construct a composite high-efficiency adsorbent with a synergistic adsorption effect, wherein the amino and hydroxyl groups in the chitosan quaternary ammonium salt are key active sites, which can form hydrogen bonds or ionic bonds with polar functional groups (such as carboxyl groups, sulfonic acid groups, etc.) in dye molecules, which not only effectively improves the adsorption performance, but also increases the structural stability of the adsorbent and the density of active sites. Sodium lignin sulfate has a large number of hydroxyl groups and benzene rings, wherein the benzene rings can form non-covalent interactions with aromatic rings in dye molecules through the π-π stacking effect, further significantly improving the adsorption capacity and selectivity of the adsorbent. The present invention successfully modifies chitosan quaternary ammonium salt through isocyanate and a catalyst, and the synergistic effect between a large number of amino groups, hydroxyl groups, benzene rings, and carbonyl groups in the modified adsorbent can significantly optimize the chemical and physical adsorption processes of the adsorbent, so that it has the characteristics of high-efficiency adsorption.
[0013] Furthermore, the mass ratio of the sodium lignin sulfate, chitosan quaternary ammonium salt and isocyanate is (5-16): (4-16): (13-26).
[0014] Furthermore, the mass ratio of the sodium lignin sulfate, chitosan quaternary ammonium salt and isocyanate is (9-12):(8-11):17.
[0015] Furthermore, the amount of the catalyst used is 5% to 10% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isocyanate.
[0016] Furthermore, the organic solvent in step S1 is xylene.
[0017] Furthermore, the mixing method in step S1 is ultrasonic vibration.
[0018] Furthermore, the mass ratio of the sodium lignin sulfate to the organic solvent in the slurry A is 15:(35-52).
[0019] Furthermore, the mass ratio of the chitosan quaternary ammonium salt to the organic solvent in the slurry B is 12:(35-52).
[0020] Furthermore, the inert gas in step S3 is nitrogen or argon.
[0021] Furthermore, the isocyanate in step S3 is isophorone diisocyanate.
[0022] Furthermore, the catalyst in step S3 is dibutyltin dilaurate.
[0023] Furthermore, the reaction time in step S3 is 6 to 8 h.
[0024] Furthermore, the biomass-based efficient adsorbent has an adsorption capacity of up to 192 mg / g for acid scarlet dye.
[0025] In a second aspect, the present invention provides a biomass-based high-efficiency adsorbent prepared by the method.
[0026] In a third aspect, the present invention provides the use of the biomass-based efficient adsorbent in the treatment of organic dyes or polluted wastewater.
[0027] Compared with the prior art, the present invention is beneficial in that:
[0028] (1) The present invention uses sodium lignin sulfate to modify chitosan quaternary ammonium salt to construct a biomass-based high-efficiency adsorbent with a synergistic adsorption effect. The synergistic effect of a large number of amino, hydroxyl, benzene ring and carbonyl groups in the adsorbent significantly enhances the chemical and physical adsorption process between the adsorbent material and the dye molecules, making it have the characteristics of high-efficiency adsorption.
[0029] (2) The isocyanate in the present invention plays a key role. Under the cross-linking effect of isocyanate, chitosan quaternary ammonium salt and sodium lignin sulfate are successfully constructed into a composite material with a rigid macromolecular network. At the same time, the polarized structure of the carbonyl group in isocyanate enables the adsorbent and the organic dye molecules to be more tightly combined, significantly improving the mechanical strength of the adsorbent material and its dispersibility in water. In addition, isocyanate causes the chitosan quaternary ammonium salt to undergo an open-chain reaction through a nucleophilic reaction, exposing more active sites such as amino groups and hydroxyl groups, further enhancing the adsorption capacity of organic dyes, ensuring that the adsorbent can be evenly dispersed in the aqueous phase, and providing a basic support for achieving efficient adsorption performance.
[0030] (3) The chitosan quaternary ammonium salt and sodium lignin sulfate used in the biomass-based high-efficiency adsorbent provided by the present invention are renewable biomass raw materials, which achieves efficient removal of organic dyes in papermaking wastewater, reduces the production cost of the adsorbent, and provides a new way to recycle waste paper pulp. Through resource recycling and environmentally friendly design, the present invention provides a practical solution for sustainable development and ecological environmental protection, while promoting the efficient development and application of biomass materials, showing important economic and social value.
[0031] (4) The preparation method of the biomass-based high-efficiency adsorbent provided by the present invention is simple and easy to operate, does not involve expensive and dangerous chemicals, is green and environmentally friendly, and is conducive to large-scale production. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides a method for preparing a biomass-based high-efficiency adsorbent, comprising the following steps:
[0034] S1. Mix sodium lignin sulfate and xylene by ultrasonic vibration to obtain sodium lignin sulfate slurry, which is recorded as slurry A;
[0035] S2, mixing chitosan quaternary ammonium salt and xylene by ultrasonic vibration to obtain chitosan quaternary ammonium salt slurry, recorded as slurry B;
[0036] S3. Under the protection of inert gas, the slurry A and the slurry B are evenly mixed, and isophorone diisocyanate and dibutyltin dilaurate are added. After reacting at 100-110° C., the mixture is filtered, washed, dried, ground, and sieved to obtain a biomass-based high-efficiency adsorbent.
[0037] In some examples, the mass ratio of the sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate is (5-16): (4-16): (13-26).
[0038] In some examples, the amount of dibutyltin dilaurate is 5% to 10% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate.
[0039] In some examples, the mass ratio of sodium lignin sulfate to xylene in slurry A is 15:(35-52); the mass ratio of chitosan quaternary ammonium salt to xylene in slurry B is 12:(35-52).
[0040] In some examples, the inert gas in step S3 is nitrogen or argon.
[0041] In some examples, the reaction time in step S3 is 6 to 8 hours.
[0042] In some examples, the biomass-based efficient adsorbent has an adsorption capacity of up to 192 mg / g of acid scarlet dye.
[0043] In the following specific examples, unless otherwise specified, all the raw materials and reagents used were purchased conventionally.
[0044] Example 1
[0045] A highly efficient adsorbent based on biomass, the preparation steps are as follows:
[0046] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0047] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0048] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 5:16:26, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass-based high-efficiency adsorbent.
[0049] Example 2
[0050] A highly efficient adsorbent based on biomass, the preparation steps are as follows:
[0051] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0052] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0053] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 8:13:20, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass-based high-efficiency adsorbent.
[0054] Example 3
[0055] A highly efficient adsorbent based on biomass, the preparation steps are as follows:
[0056] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0057] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0058] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 11:10:17, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass-based high-efficiency adsorbent.
[0059] Example 4
[0060] A highly efficient adsorbent based on biomass, the preparation steps are as follows:
[0061] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0062] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0063] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 13:7:15, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 ° C. Finally, filter and wash with deionized water for 3 times, dry at 80 ° C for 12 h, grind and pass through a 200 mesh sieve to obtain a high-efficiency adsorbent based on biomass.
[0064] Example 5
[0065] A highly efficient adsorbent based on biomass, the preparation steps are as follows:
[0066] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0067] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0068] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 16:4:13, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a high-efficiency adsorbent based on biomass.
[0069] Comparative Example 1
[0070] A chitosan quaternary ammonium salt adsorbent, the preparation steps are as follows:
[0071] S1. Add chitosan quaternary ammonium salt and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration, which is recorded as slurry A;
[0072] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve, which was recorded as slurry B;
[0073] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of chitosan quaternary ammonium salt and isophorone diisocyanate 21:17, and the amount of dibutyltin dilaurate was 8% of the total mass of chitosan quaternary ammonium salt and isophorone diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and passed through a 200-mesh sieve to obtain a chitosan quaternary ammonium salt adsorbent.
[0074] Comparative Example 2
[0075] A biomass-based adsorbent, the preparation steps are as follows:
[0076] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0077] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0078] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then dibutyltin dilaurate was added to make the mass ratio of sodium lignin sulfate and chitosan quaternary ammonium salt 11:10, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate and chitosan quaternary ammonium salt, and stirred at 105 °C for 7 h. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and sieved through a 200-mesh sieve to obtain a biomass-based adsorbent.
[0079] Comparative Example 3
[0080] A sodium sulfate lignin adsorbent, the preparation steps are as follows:
[0081] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration, which is recorded as slurry A;
[0082] S2, adding sodium lignin sulfate and xylene in a mass ratio of 12:43 into a beaker, and dispersing and dissolving by ultrasonic vibration is recorded as slurry B;
[0083] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate and isophorone diisocyanate 21:17, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate and isophorone diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and passed through a 200-mesh sieve to obtain a sodium lignin sulfate adsorbent.
[0084] Comparative Example 4
[0085] A biomass-based adsorbent, the preparation steps are as follows:
[0086] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0087] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0088] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 3:18:17, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass-based adsorbent.
[0089] Comparative Example 5
[0090] A biomass-based adsorbent, the preparation steps are as follows:
[0091] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0092] S2, chitosan quaternary ammonium salt and xylene were added into a beaker at a mass ratio of 12:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0093] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then isophorone diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate 19:2:17, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, chitosan quaternary ammonium salt, and isophorone diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass-based adsorbent.
[0094] Application Examples
[0095] Analytical grade reagent acid scarlet was added to deionized water to prepare 1 L of acid scarlet solution with an initial concentration of 200 mg / L. Then 20 mg of adsorbent was weighed and added to the acid scarlet solution. The mixture was stirred at a constant speed for 3 h at 25 °C. The concentration of acid scarlet after adsorption was measured by atomic absorption spectrophotometry, and the adsorption amount was calculated. The test results are shown in Table 1.
[0096] The equilibrium adsorption amount mentioned in the test is the result of the adsorbent reaching equilibrium by oscillating adsorption of a certain concentration of organic dye solution. The concentration of organic dye before and after adsorption is determined by atomic absorption spectrophotometry, and the adsorption amount is calculated as follows:
[0097]
[0098] In the formula, is the equilibrium adsorption capacity, the unit is mg / g, C o is the initial concentration of the organic dye in the solution before adsorption, expressed in mg / L, C e is the equilibrium concentration of the organic dye in the remaining solution after adsorption, recorded in mg / L, m is the mass of the adsorbent, recorded in g, and V is the volume of the organic dye solution, recorded in L.
[0099] Table 1: Test results of adsorption of acid scarlet by adsorbents prepared in Examples 1 to 5 and Comparative Examples 1 to 5
[0100]
[0101] As can be seen from Table 1, the adsorbent prepared in Example 3 has the highest content of acid scarlet adsorbed, and the adsorbent prepared in Comparative Example 1 has the lowest content of acid scarlet adsorbed. Compared with Example 3, Comparative Example 1 uses chitosan quaternary ammonium salt as a raw material, and under the action of isocyanate and a catalyst, the chitosan quaternary ammonium salt undergoes a cross-linking reaction within or between molecules to obtain a chitosan quaternary ammonium salt adsorbent, and its adsorption amount is much lower than that of the biomass-based high-efficiency adsorbent prepared by the present invention. The reason may be that the natural chitosan quaternary ammonium salt only has its own adsorption groups and a small amount of carbonyl and phenyl groups brought by isocyanate, and its adsorption effect on acid scarlet is relatively limited; compared with Example 3, isophorone diisocyanate is not added in Comparative Example 2, and the chitosan quaternary ammonium salt and lignin sulfate are not cross-linked. There is no cross-linking reaction between sodium, and it is only combined by electrostatic adsorption such as hydrogen bonds, so it cannot effectively improve the dispersion effect of the adsorbent, so that the adsorption amount of the adsorbent in Comparative Example 2 is poor; compared with Example 3, Comparative Example 3 uses sodium lignin sulfate as a raw material, and under the action of isocyanate and a catalyst, sodium lignin sulfate undergoes a cross-linking reaction within or between molecules to obtain a sodium lignin sulfate adsorbent, and its adsorption amount is much lower than the adsorption amount of the biomass-based high-efficiency adsorbent prepared by the present invention. Although the hydroxyl and benzene ring groups contained in sodium lignin sulfate have a certain adsorption effect on acid scarlet, the adsorption effect is limited. Compared with Example 3, in Comparative Example 4, sodium lignin sulfate is reduced, and the dosage of chitosan quaternary ammonium salt is increased to make the mass ratio 3:18. The adsorption amount of the prepared adsorbent is poorer than that of the adsorbent in the present invention. The reason may be that the very small dosage of sodium lignin sulfate leads to a reduction in the adsorption sites provided by sodium lignin sulfate, and a large amount of chitosan quaternary ammonium salt does not participate in the cross-linking reaction. Compared with Example 3, in Comparative Example 5, sodium lignin sulfate was added and the amount of chitosan quaternary ammonium salt was reduced. The reason for the decrease in adsorption amount was the same as that in Comparative Example 4, which was due to the reduction of active sites.
[0102] In summary, in the presence of a catalyst dibutyltin dilaurate, the present invention uses a specific ratio of sodium lignin sulfate and isocyanate to modify chitosan quaternary ammonium salt to obtain a biomass-based efficient adsorbent. The method of the present invention is simple to operate and low in cost. The prepared biomass-based efficient adsorbent has excellent dye adsorption capacity, wherein the adsorbent has an adsorption amount of up to 192 mg / g for acid scarlet dye, and can be widely used in the treatment of organic dyes or polluted wastewater.
[0103] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for preparing a biomass-based high-efficiency adsorbent, characterized in that: The steps include: S1, mixing sodium lignin sulfate and an organic solvent evenly to obtain sodium lignin sulfate slurry, recorded as slurry A; S2, mixing chitosan quaternary ammonium salt and organic solvent uniformly to obtain chitosan quaternary ammonium salt slurry, recorded as slurry B; S3. Under the protection of inert gas, the slurry A and the slurry B are mixed evenly, and then isocyanate and a catalyst are added, and the mixture is reacted at 100-110° C. to obtain a biomass-based high-efficiency adsorbent.
2. The method for preparing a biomass-based efficient adsorbent according to claim 1, characterized in that: The mass ratio of the sodium lignin sulfate, chitosan quaternary ammonium salt and isocyanate is (5-16): (4-16): (13-26).
3. The method for preparing a biomass-based efficient adsorbent according to claim 2, characterized in that: The mass ratio of the sodium lignin sulfate, chitosan quaternary ammonium salt and isocyanate is (9-12): (8-11):
17.
4. The method for preparing a biomass-based efficient adsorbent according to claim 1, characterized in that: The reaction time in step S3 is 6 to 8 h.
5. The method for preparing a biomass-based efficient adsorbent according to claim 1, characterized in that: The mass ratio of sodium lignin sulfate to organic solvent in slurry A is 15:(35-52).
6. The method for preparing a biomass-based efficient adsorbent according to claim 1, characterized in that: The mass ratio of the chitosan quaternary ammonium salt to the organic solvent in the slurry B is 12:(35-52).
7. The method for preparing a biomass-based efficient adsorbent according to claim 1, characterized in that: The isocyanate in step S3 is isophorone diisocyanate.
8. The method for preparing a biomass-based efficient adsorbent according to claim 1, characterized in that: The catalyst in step S3 is dibutyltin dilaurate.
9. A biomass-based high-efficiency adsorbent prepared by the method according to any one of claims 1 to 8.
10. Use of the biomass-based high-efficiency adsorbent as claimed in claim 9 in the treatment of organic dyes or polluted wastewater.